Pharmacological landscape of FDA-approved anticancer drugs reveals sensitivities to ixabepilone, romidepsin, omacetaxine, and carfilzomib in aggressive meningiomas - Jungwirth, Gerhard; Yu, Tao; Liu, Fang; Cao, Junguo; Alaa Eddine, Montadar; Moustafa, Mahmoud; Abdollahi, Amir; Warta, Rolf; Unterberg, Andreas; Herold-Mende, Christel (Clinical cancer research, 2023)
To date, there are no systemic treatment options for patients with recurrent or refractory meningioma.To identify effective drugs, we performed a large-scale drug screening using FDA-approved drugs on several meningioma cell lines. The impact of the top four compounds was assessed on cell viability, proliferation, colony formation, migration, and apoptosis. In addition, the antineoplastic effects of the selected drugs were validated in a heterotopic xenograft mouse model.Analyses of the viability of meningioma cells treated with 119 antineoplastic FDA-approved drugs resulted in categorization into sensitive and resistant drug-response groups based on the mean IC50 values and peak serum concentrations (Cmax) in patients. Eighty drugs, including 15 alkylating agents, 14 antimetabolites, and 13 tyrosine kinase inhibitors, were classified as resistant (IC50 > Cmax). The sensitive drug-response group (n = 29, IC50 < Cmax) included RNA/protein synthesis inhibitors, proteasome inhibitors, topoisomerase, tyrosine-kinase, and partial histone deacetylase and microtubule inhibitors. The IC50 value of the four most effective compounds (carfilzomib, omacetaxine, ixabepilone, and romidepsin) ranged from 0.12 to 9.5 nmol/L. Most of them caused cell-cycle arrest in the G2-M-phase and induced apoptosis. Furthermore, all drugs except romidepsin significantly inhibited tumor growth in vivo. The strongest antineoplastic effect was observed for ixabepilone, which reduced tumor volume by 86%.In summary, a large-scale drug screening provides a comprehensive insight into the anti-meningioma activities of FDA-approved drugs, and identified carfilzomib, omacetaxine, ixabepilone, and romidepsin as novel potent antineoplastic agents for the treatment of aggressive meningiomas. The most pronounced effects were observed with ixabepilone mandating for further clinical investigation.
Gesehen am 16.10.2023